An Exploration of the Strategies ESL Teachers Use in Teaching English Grammar in Selected Rural Ghanaian Junior High Schools - Adawu, Anthony; Bintul, Joshua Kwabena Nbiba (International Journal of Language and Literary Studies, 2025)
The persistent difficulty of learners in rural Ghanaian junior high schools (JHS) in mastering English grammar raises important questions about the instructional strategies employed by teachers. This study explored the strategies that ESL teachers adopt in teaching English grammar in selected rural JHS in Ghana, specifically Nkwanta North context. Anchored in Vygotsky’s (1978) Zone of Proximal Development and scaffolding, the study adopted a qualitative case study design to gain an in-depth understanding of grammar teaching practices within these environments. Ten English language teachers were purposively selected from public JHS. Data was collected through semi-structured interviews and classroom observations, and analyzed thematically using Saldaña’s (2021) in vivo and pattern coding methods. Findings revealed that teachers employed group discussions, role-play, storytelling, sentence correction, and construction to foster grammatical competence. Despite the absence of adequate instructional materials, teachers exhibited remarkable pedagogical adaptability through the use of improvised teaching aids to support grammar instruction. The study concludes that effective grammar teaching in rural Ghanaian classrooms is sustained by context-responsive scaffolding, collaborative learning, and creative resource utilization. It recommends that stakeholders should strengthen regular in-service training, focused on interactive grammar pedagogy, and contextual adaptation of teaching aids to enhance learner outcomes in resource-constrained settings.